Correlation between pre-operative and final histological diagnosis on endometrial cancer. Issue 5 (4th January 2019) - Shiozaki, Takaya; Miwa, Maiko; Sakuma, Toshiko; Suzuki, Kazuhiro; Kogiku, Ai; Yamamoto, Kasumi; Senda, Tokihiro; Yano, Hiroko; Kitai, Miho; Matsuoka, Kazuko; Sudo, Tamotsu; Nagao, Shoji; et al.
Abstract : Objective: We conducted a retrospective study to evaluate the correlation between pre-operative and post-operative histological diagnoses on endometrial cancer, and to describe the treatments and outcomes when post-operative diagnoses are downgraded from pre-operative histology. Methods: Patients who underwent surgery for endometrial cancer in our facility between 2010 and 2013 were enrolled in the study. The definition of downgrade discordance is in accordance with the following criteria: 1) the pre-operative and post-operative histological diagnoses were both endometrioid and the final pathology was a lower grade than the pre-operative pathology and 2) the pre-operative diagnosis was not endometrioid, whereas the post-operative diagnosis was endometrioid grade 2 or less. Results: A total of 250 patients were enrolled, and the concordance rates were 56% for endometrioid adenocarcinoma grade 1 (EMG1), 67% for EMG2, 67% for EMG3, 82% for carcinosarcoma, 71% for serous carcinoma, and 67% for clear cell carcinoma. Eighteen cases (6.6%) were identified as downgrade discordancy. Of the 18 patients, the triage for adjuvant therapy remained the same for 15 cases (83%), all of whom had no evidence of disease at their last visit. Three cases had discordances with respect to triage for adjuvant therapy; the therapies were triaged based on post-operative diagnosis. Of these patients one had a recurrence. Conclusions: Good correlation was observed between pre-operative and final histological diagnoses of endometrioid carcinoma (56%–67%) and type 2 carcinoma (67%–82%). Approximately 7% (18/250) of patients had downgrade discordancy; however, triage for adjuvant therapy did not change for approximately 80% (15/18) of the patients with downgrade discordancy. Further studies are needed to evaluate the effectiveness of triages that are based on post-operative diagnoses.